2001
DOI: 10.1046/j.1472-4642.2001.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and endemism of plant and bird communities along two gradients of elevation, humidity and land use in the Bolivian Andes

Abstract: Abstract.We studied the patterns of species richness and range–size rarity (as a measure of endemism) of two plant groups (Pteridophyta, Bromeliaceae) and birds along two gradients of elevation, humidity and human land use in a forested Andean valley. Both transects covered the transition from an arid valley bottom through a cloud forest zone to relictual high‐elevation Polylepis forest, but transects differed in overall precipitation. Plants were surveyed in 88 plots of 400 m2 each, while birds were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 48 publications
6
86
0
4
Order By: Relevance
“…The pattern of the avian community of the present study varies from that reported by many previous studies conducted on bird species richness along altitudinal gradients mostly in temperate regions. Most such studies have found the highest species richness at low elevation such as in rain forest of eastern Andes Peru (Terborgh 1971;Terborgh & Weske 1975) or mid elevation such as in Peruvian Andes (Rahbek 1995(Rahbek , 2005, Madagascan rain forest (Colwell & Lees 2000), Bolwian Andes South American Forest (Kessler et al 2001), Columbian Andes forest (Kattan & Franco 2004), urban/subtropical to subarctic forest in Taiwan (Lee et al 2004;Ding et al 2005). In the present study the higher BSD and BSR observed in high altitude areas may be connected to the higher plant diversity.…”
Section: Discussionsupporting
confidence: 53%
“…The pattern of the avian community of the present study varies from that reported by many previous studies conducted on bird species richness along altitudinal gradients mostly in temperate regions. Most such studies have found the highest species richness at low elevation such as in rain forest of eastern Andes Peru (Terborgh 1971;Terborgh & Weske 1975) or mid elevation such as in Peruvian Andes (Rahbek 1995(Rahbek , 2005, Madagascan rain forest (Colwell & Lees 2000), Bolwian Andes South American Forest (Kessler et al 2001), Columbian Andes forest (Kattan & Franco 2004), urban/subtropical to subarctic forest in Taiwan (Lee et al 2004;Ding et al 2005). In the present study the higher BSD and BSR observed in high altitude areas may be connected to the higher plant diversity.…”
Section: Discussionsupporting
confidence: 53%
“…Organisms showing mid-elevation peaks in species richness include epiphytic ferns [58], vascular plants and lichens [59], moths [60], ants [61,62], birds [58,63], and small mammals [64]. The reasons for these patterns are varied and difficult to disentangle.…”
Section: Species Richness and Environmental Gradientsmentioning
confidence: 99%
“…According to Kessler et al [58], for example, the mid-elevation peak in bird and epiphytic fern diversity in the Bolivian Andes coincides with peaks in primary productivity, foliage height (i.e., spatial heterogeneity), and land use (i.e., disturbance).…”
Section: Species Richness and Environmental Gradientsmentioning
confidence: 99%
“…Rahbek [7] demonstrated that hump-shaped relationship with maximum species numbers at midelevations. Different elevational richness pattern may be due to (a) an overall decline of species richness with increasing altitude [33], (b) a plateau of species being the richest at lower altitude then declining towards the highest elevations [34], and (c) a midelevation peak of species richness [35,36]. Padmanaban [18] reported that cockroach diversity and abundance were the maximum in the middle altitudes in comparison with those in the higher and lower altitudes of Alagar hills reserve forest., Isabel [23] also emphasized that arthropod species diversity was higher in midelevations compared to that in lower and higher elevations of Alagar hills.…”
Section: Discussionmentioning
confidence: 99%